Prevenção de luto complicado em cuidados paliativos: percepções dos profissionais de saúde acerca de suas contribuições nesse processo - Braz, Mariana Sarkis (2013)
Palliative care seek quality of life based primarily on prevention and relief of suffering of patients who have life threatening diseases, encompassing the areas of physical, psychosocial and spiritual. Furthermore, extending the post-mortem patient, it offers support the family support in the grieving process. The theme provides discussions of education for death and dying process for health care professionals who are educated mostly geared towards the enhancement of technical knowledge at the expense of a humanist education, which removes the theme of death as the focus of learning. This qualitative study aimed to understand and analyze the training of professionals in relation to dying patient and their perception regarding their contributions to the prevention of complicated grief care unit. The Attachment Theory grounded this research theoretically, providing support for the analysis. Health professionals who integrate palliative care teams voluntarily participated in this research . A questionnaire was used to obtain academic and professional data, besides courses taken. A semi-structured interview allowed us to understand the following topics: the choice of working in palliative care, the strategies used (by oneself and by the care unit) on a daily basis to deal with the issue of the dying process and the perception of its contribution to the prevention of complicated grief of patient and family. The results confirmed that the training of professionals in relation to the dying process is scarce. Moreover, it was observed that health professionals working in palliative care have attachment behaviors, identified as natural in this context, and that ends up to make it harder to realize that those are important contributions to prevent grief from becoming complicated in the care unit